Private Well 101: Drinking Water Standards - Yilin Zhuang; Andrea Albertin; Arthur G. Hornsby (EDIS)
Drinking water comes from a variety of sources, including public water systems, private wells, or bottled water. While public water systems are monitored under the federal Safe Drinking Water Act, private wells are not regulated. Private well users are responsible for the management and protection of their wells and water quality. This publication of the Department of Soil, Water, and Ecosystem Sciences is for Florida homeowners who are interested in learning more about drinking water standards. It also serves as a reference for well owners to understand their drinking water quality. Major revision by Yilin Zhuang, Andrea Albertin, and Arthur G. Hornsby; 10 pages. https://edis.ifas.ufl.edu/ss297